Data in online version of the ‘Dictionary of Medieval Latin from British Sources’ (DMLBS) - Ashdowne, R (University of Oxford, 2016)
The DMLBS is distinctive not only for the breadth of its coverage but also for the fact that it is wholly based on original research, i.e. on a fresh reading of medieval Latin texts for this specific purpose, where possible in the best available source, whether that be original manuscripts or modern critical editions. (The method is that used by other major dictionaries, such as the monumental Oxford English Dictionary and, for Latin, the Oxford Latin Dictionary, the Thesaurus Linguae Latinae.) In the nearly 50 years of drafting the Dictionary, different editorial practices and conventions have inevitably created a text that varies significantly from the earliest fascicules to the final ones while remaining recognizably the same underlying work. Many of these variations have been the result of conscious decisions, other simply the result of the Dictionary being the work of many people over many years.